Effects of meteorological factors on fruit qualities of 'Fuji' apple in Korea - Yeong, B. S.; Cheol, C.; Hitoshi, U. (International Journal of Horticultural Science, 2001)
'Fuji' apples from five different growing regions in Korea were analyzed for internal and external quality attributes which included fruit shape, color and sugar. Significant relationships were observed between final fruit color (a*) and air temperature in August. Red color was poorly developed where the average temperature in August was over 25 oC. The sugar composition was significantly different depending on region. The sucrose content decreased with increasing temperature above 16 oC during the harvest season. The fruit shape was not affected by agro-climatic conditions in this study.